Arc-proof fabric and preparation method thereof
By synthesizing a three-dimensional porous composite protective network in situ within the fabric fibers, the contradiction between protective performance and comfort in existing technologies has been resolved, achieving a synergistic improvement in the durability and comfort of arc-proof fabrics under high protective performance.
Patent Information
- Application Number
- CN202511281145.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-11-04
AI Technical Summary
Existing arc-proof fabrics often sacrifice wearing comfort in pursuit of high protective performance, while surface-coated fabrics are prone to performance degradation during long-term use, failing to achieve a synergistic improvement in both long-term protective performance and comfort.
By synthesizing a three-dimensional porous composite protective network in situ within the fabric fiber structure, and by grafting active functional groups using plasma treatment, combined with multi-stage precursor solution infiltration and hydrothermal synthesis, a synergistic structure of inorganic oxide network and two-dimensional nanosheet material is formed, achieving deep integration of protective function with the base fabric.
It achieves a synergistic improvement in protective performance durability and comfort. The three-dimensional porous composite network forms a strong whole with the base fabric fibers, and the protective performance is not reduced. The fabric is lightweight, soft and breathable, and can withstand repeated friction and washing in industrial environments.
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of textile materials and safety protection, and specifically relates to an arc-proof fabric and a preparation method thereof. BACKGROUND
[0002] In high-risk operating environments such as electric power, chemical industry, metallurgy, etc., arc flash explosion, as a sudden and high-energy electrical accident, poses a serious threat to the life safety of practitioners. In order to effectively avoid or reduce the secondary burns caused by arc heat energy to the human body, the development of arc-proof fabrics with excellent protective performance has become a crucial technical branch in the field of personal protective equipment (PPE). The core technical goal of such special functional textiles is to instantaneously block or dissipate the high-intensity heat flow generated by the arc, while maintaining the structural integrity of the material itself, avoiding melting and dripping, so as to provide a critical escape window for the wearer. After years of technical evolution, two mainstream technical paths represented by modified fiber blending and functional coating finishing have been formed in this field.
[0003] Specifically, early technical solutions focus on the improvement of the material itself, that is, by blending essential flame-retardant fibers (such as aramid fibers, polybenzimidazole fibers, etc.) with other fibers in a specific ratio, or chemically modifying conventional fibers to give the fabric inherent flame-retardant properties. On this basis, to cope with higher energy levels of arc impact, the industry has further developed more complex fabric structure designs. For example, the technical solution disclosed in Chinese Patent CN101973148A is a typical structure-enhanced protective fabric. This solution forms a cross double-layer composite tube structure by precisely weaving a flame-retardant outer layer, a heat-insulating layer, and a flame-retardant inner layer. The design principle is to use the air layer between the multiple layers of fabric as an efficient heat-insulating medium, and to absorb and disperse arc energy with the synergistic effect of the inner and outer layers of materials. This technology, through physical layer superposition and structure optimization, does achieve a higher protection level under certain conditions, providing an effective engineering approach to solving the problem of instantaneous heat protection in high-risk scenarios. At the same time, another technical path focuses on the functional modification of the fabric surface. For example, Chinese Patent CN116289236A discloses a preparation method of an arc-proof coated fabric, the core of which is to mix inorganic fillers such as expandable graphite with a high polymer matrix and attach them to the surface of the base fabric through a coating process. When exposed to arc heat, the expandable graphite rapidly expands in volume, forming a dense, porous carbon heat-insulating layer on the surface of the fabric. This carbon layer can effectively block heat transfer and play a role in consuming heat energy. The advantage of this solution is that the preparation process is relatively flexible, and it can give the base fabric excellent arc-proof function without significantly changing the base fabric itself.
[0004] However, with the continuous development of related technologies and the increasingly stringent requirements of application scenarios on the comprehensive performance of personal protective equipment, some inherent characteristics of the above technical solutions at the principle level gradually reveal limitations in dealing with new challenges, and point to a deep technical contradiction: the inherent conflict between the persistent stability of protective performance and the wearing comfort. For the former, i.e. the structure-enhanced fabric, the protective level shows a strong positive correlation with the number of layers, the gram weight and the thickness of the fabric. In order to achieve higher protection standards, it is necessary to increase the physical stacking of the fabric, which directly leads to a significant increase in the overall weight and rigidity of the fabric, while greatly sacrificing the moisture permeability. In high-intensity working environments, such low comfort not only affects the flexibility and work efficiency of the operators, but also may cause physiological safety risks such as heat stress, so that the protective equipment, while solving one safety problem, has also spawned another potential health hazard. Its complex composite weaving process also brings real problems such as high production cost and difficult process control. For the latter, i.e. the surface-coated fabric, although it can balance the protection and softness of the base fabric in the initial state, its technical weakness lies in that the protective function carrier (coating) and the base (fabric) are only combined by physical or chemical bonding force, and they are not an organic whole. This leads to the inherent deficiency of the durability of the protective system. Under the repeated action of daily wear and tear and industrial washing, the interfacial bonding force between the coating and the fiber substrate will gradually weaken, and microscopic cracking, peeling and even peeling will inevitably occur, resulting in significant attenuation or even failure of the protective performance. In order to increase the amount of adhesive or perform high-temperature baking to improve the bonding strength, the fabric will often become stiff, again falling into the dilemma of sacrificing comfort for performance.
[0005] In summary, the existing technical path seems to be in a dilemma: pursuing absolute protection in structure inevitably sacrifices comfort; and pursuing flexibility and comfort of surface functionalization cannot guarantee the long-term stability and reliability of protective performance. This non-integrated design idea of "external hanging" or "stacking" between protective function and fabric body is the fundamental reason why performance cannot be synergistically improved. Therefore, how to break through the existing technical framework and develop a kind of deep and stable integration of high-efficiency protective units and fabric substrates, so that the protective performance is not only efficient, but also can withstand the test of actual use environment, while retaining the original comfortable wearing performance of the fabric to the maximum extent, has become the key challenge and technical problem to be solved for the technical personnel in the field. SUMMARY
[0006] The technical problems to be solved by the present application are to provide an anti-arc fabric and a preparation method thereof, aiming to overcome the inherent contradiction between the durability and stability of protection performance and the wearing comfort caused by the non-integrated stacking or attachment relationship between the protection function unit and the fabric substrate in the prior art. The prior art either increases the fabric grammage and thickness to improve the protection level, thereby sacrificing the comfort; or imparts the protection function through surface coating, but the coating is prone to peeling under repeated bending and washing, resulting in attenuation of the protection performance. The present application aims to realize the coordination and unity of anti-arc performance, durability and comfort through a technical path of integrating the functional protection network in situ into the fabric fiber structure.
[0007] To achieve the above-mentioned application purposes, the present application provides an anti-arc fabric and a preparation method thereof.
[0008] According to one aspect of the present application, a preparation method of an anti-arc fabric is provided, the method comprising the following steps: Step S1, substrate pretreatment and surface activation step: selecting a woven fabric or knitted fabric composed of inherently flame-retardant fibers as a base cloth, placing the base cloth in a vacuum plasma treatment device, and performing low-temperature plasma glow discharge treatment in a mixed atmosphere of inert gas and active gas to etch and graft oxygen-containing active functional groups on the surface of single fibers of the base cloth; Step S2, multi-stage precursor solution penetration and loading step: this step includes a first precursor penetration and loading step and a second precursor penetration and loading step in sequence. First, the base cloth subjected to the surface activation treatment of step S1 is immersed in a first precursor solution containing two-dimensional nanosheet materials, and ultrasonic oscillation is applied to make the two-dimensional nanosheet materials uniformly adsorbed and coated on the surface of single fibers and the internal voids of fiber bundles of the base cloth, and then excess solution is removed through a padding device. Then, the base cloth loaded with two-dimensional nanosheet materials is immersed in a second precursor solution formed by dissolving the chemical precursor of the inorganic network skeleton in a solvent, and the second precursor solution is fully penetrated into the internal fiber bundles and closely contacted with the loaded two-dimensional nanosheet materials again through the padding device; Step S3, in-situ hydrothermal synthesis and thermal shock forming step of the integrated protective network: the substrate loaded with two precursors in step S2 is placed in a sealed high-pressure reaction kettle, a certain amount of pure water is injected, and then sealed for hydrothermal reaction treatment. In this process, the chemical precursors in the second precursor solution undergo hydrolysis and polycondensation reaction to generate in-situ inorganic oxide network on the surface of the substrate fibers and in the interstitial space of the fibers; at the same time, part of the functional groups of the two-dimensional nanosheet material are reduced. After the hydrothermal reaction is completed, the substrate is taken out and dried, and then placed in an inert atmosphere protection furnace provided with a rapid heating device for high-temperature rapid thermal shock treatment. In this process, the residual oxygen-containing functional groups on the surface of the two-dimensional nanosheet material are thermally decomposed to generate gas, which drives the two-dimensional nanosheet layer to peel off and expand to form a three-dimensional porous structure, and penetrate the previously generated inorganic oxide network, together forming a three-dimensional porous composite protective network deeply anchored with the substrate fiber structure; Step S4, finishing and setting step: the composite fabric formed after step S3 is treated is ultrasonically cleaned in deionized water to remove any unreacted residues and physically adsorbed impurities. After cleaning, the fabric is soft finished and heat set to obtain the anti-electric arc fabric.
[0009] Further, in the step S1, the substrate is preferably a woven fabric made of meta-aramid fibers and para-aramid fibers mixed at a mass ratio of (90-95):(5-8), and (1-3) of conductive fibers by weight, and woven by twill weave. The areal density of the substrate is controlled in the range of 180-260 g / m2. The mixed atmosphere used in the low-temperature plasma treatment is composed of argon with a volume flow rate of 80-120 standard cubic centimeters per minute (sccm) and oxygen with a volume flow rate of 10-30 standard cubic centimeters per minute (sccm). The power of the glow discharge treatment is set to 200-400 W, the vacuum degree in the treatment chamber is maintained at 15-50 Pa, and the treatment time is 90-240 s. Through this step, active functional groups mainly including hydroxyl (-OH) and carboxyl (-COOH) are formed on the surface of the aramid fibers.
[0010] Further, in the step S2, the first precursor solution is an aqueous dispersion of graphene oxide (GO). The graphene oxide is prepared by a modified Hummers method, with a single sheet lateral size distribution between 0.5 microns and 5 microns, and a thickness of 0.8 nanometers to 1.2 nanometers. The mass concentration of the aqueous graphene oxide dispersion is 1.0 milligram per milliliter to 5.0 milligrams per milliliter. The frequency of the ultrasonic oscillation is 40 kilohertz, and the oscillation time is 30 minutes to 90 minutes. The roll device is a double roll mill, with a roll reduction ratio precisely controlled between 70% and 95%. The second precursor solution is a sol-gel precursor solution prepared by mixing 100 parts by weight of anhydrous ethanol as a main solvent, 10-15 parts by weight of tetraethyl orthosilicate (TEOS), and 1-3 parts by weight of aluminum isopropoxide, under magnetic stirring until uniform. Subsequently, 4-8 parts by weight of deionized water is added to the mixed solution, and 0.2-0.6 parts by weight of hydrochloric acid with a concentration of 1 mole per liter is added dropwise as a catalyst under ice water bath conditions, with continuous stirring for 2 hours to 4 hours until a clear, transparent, and stable sol-gel precursor solution is formed. After the graphene oxide-loaded base fabric is immersed in the solution, the roll reduction is also performed by the double roll mill, with a roll reduction ratio controlled between 80% and 100%.
[0011] Further, in the step S3, the hydrothermal reaction treatment is performed under the following conditions: in a high-pressure reaction kettle, the mass ratio of the base fabric to pure water is controlled to be 1:20, and the filling degree of the reaction kettle is 75%. After sealing, the reaction kettle is heated to a temperature interval of 140 degrees Celsius to 180 degrees Celsius, and maintained at this temperature for 4 hours to 8 hours. In this process, tetraethyl orthosilicate and aluminum isopropoxide are hydrolyzed and polycondensed in situ to form a silica-alumina composite hydrogel network, which is coated and anchored on the surface of the graphene oxide sheets and aramid fibers. The high-temperature rapid thermal shock treatment is performed in a tube-type rapid thermal annealing furnace. First, nitrogen gas with a purity of 99.999% is introduced into the furnace to reduce the oxygen concentration in the furnace to less than 5 parts per million (ppm). Subsequently, the furnace temperature is rapidly increased from room temperature to a target temperature of 200 degrees Celsius to 300 degrees Celsius at a temperature rise rate of greater than 30 degrees Celsius per second. When the target temperature is reached, the temperature is maintained for 30 seconds to 120 seconds. This process causes the residual oxygen-containing functional groups between the partially reduced graphene oxide (rGO) sheets to instantaneously gasify, and the generated gas pressure drives the rGO sheets to peel off, expand, and wrinkle, forming a three-dimensional graphene foam structure with micrometer- and nanometer-sized pores. The foam structure physically interpenetrates and interfacially bonds with the silica-alumina ceramic network skeleton formed in the hydrothermal stage, and is finally solidified to form the three-dimensional porous composite protective network.
[0012] Further, in the step S4, the soft finishing treatment is performed using an amino-modified polysiloxane microemulsion as a softening agent. The fabric after washing and dehydration is padded with the softening agent working solution, and then pre-dried at 100°C for 10 minutes, and finally heat-set at 150°C for 3 minutes. This step aims to restore and optimize the touch and drape of the fabric without damaging the protective structure formed inside.
[0013] According to another aspect of the present application, there is provided an arc- resistant fabric, which is composed of a base fabric and a three-dimensional porous composite protective network integrally built inside the base fabric. The base fabric is a woven or knitted fabric composed of inherently flame-retardant fibers. The three-dimensional porous composite protective network, in microstructure, conformally coats the surface of individual fibers of the base fabric and completely fills all three-dimensional interstices between fibers and between yarns, and forms an inseparable whole structure with the base fabric fibers through both chemical bonding and physical and mechanical interlocking mechanisms.
[0014] More specifically, the three-dimensional porous composite protective network is composed of the following two interpenetrating and synergistic components: a three-dimensional porous thermally conductive skeleton composed of reduced graphene oxide: the thermally conductive skeleton is a continuous, foam-like network with multi-level pore structures of micrometer and nanometer scales, which forms a through, high-thermal-conductivity channel inside the fabric. When subjected to arc high-temperature impact, the thermally conductive skeleton can instantaneously conduct and dissipate the concentrated heat flow along two-dimensional planes and three-dimensional space, thereby avoiding the high accumulation of heat at the impact point. At the same time, under high-temperature action, the surface layer of the skeleton rapidly transforms into a dense carbon layer, which plays a role in insulating thermal radiation and preventing the penetration of molten material.
[0015] an inorganic ceramic reinforcing phase interpenetrating with the thermally conductive skeleton and anchored to the base fabric fibers: the inorganic ceramic reinforcing phase is a three-dimensional network structure composed of nanoscale silica-alumina composite oxides. The ceramic reinforcing phase, in normal state, provides mechanical strength and wear resistance to the entire composite protective network; under extreme high-temperature conditions such as arc, its high melting point characteristics enable the entire protective network to maintain structural integrity, effectively inhibiting the melting and shrinking of the base fabric fibers and the rupture of the carbonized layer, thereby eliminating the occurrence of molten dripping, and providing a stable and reliable physical barrier for the wearer.
[0016] As a preferred embodiment of the present application, the base fabric is a woven fabric with an areal density of 220 g / m2, which is woven from a blend yarn of 93% by mass of meta-aramid fiber, 5% by mass of para-aramid fiber, and 2% by mass of conductive fiber, using a two-over-one twill weave. The total load of the three-dimensional porous composite protective network accounts for 10% to 25% of the final total mass of the fabric. The pore size distribution of the pores in the reduced graphene oxide heat-conducting skeleton ranges from 50 nm to 5 μm. In the inorganic ceramic reinforcing phase, the molar ratio of silicon dioxide to aluminum oxide is 10:1. The protective network and the aramid fibers of the base fabric are chemically bonded through C-O-Si chemical bonds formed in the plasma activation step.
[0017] The beneficial effects of the present application are as follows. First, the present application realizes deep integration of the protective functional units and the fabric matrix at the molecular scale and microstructure by in-situ synthesis of a three-dimensional porous composite protective network inside the fabric. Compared with traditional coating techniques, the protective network of the present application and the fiber matrix form a firm whole through chemical bonding and physical interlocking without obvious interfaces. Therefore, the fabric exhibits excellent durability and stability without significant degradation of the protective performance after multiple industrial washes, continuous rubbing, and repeated bending, thus fundamentally solving the technical problem of protective failure caused by coating peeling.
[0018] Second, the protective mechanism of the present application is multi-synergistic. The three-dimensional graphene foam skeleton provides an instantaneous and efficient heat conduction and dissipation path, and the inorganic ceramic network maintains the stability of the structure at extremely high temperatures and prevents droplet formation. This synergistic effect enables the fabric to achieve high-level arc protection performance at a lower load of functional components. Since the protective network is mainly filled in the original interstitial space of the fibers rather than forming a thick coating on the surface of the fabric, the fabric maximally retains the original lightweight, soft, breathable, and moisture-permeable properties of the base fabric while improving the protective level, significantly improving the comfort of the wearer, and solving the inherent defects of traditional high-protection-level fabrics, such as heaviness and stuffiness.
[0019] Third, the preparation method of the present application is highly controllable. By precisely adjusting the plasma treatment parameters, the concentration of the precursor solution, the hydrothermal reaction conditions, and the temperature rise rate and peak temperature of the rapid thermal annealing, the micro-morphology, pore structure, and component ratio of the final protective network can be accurately designed and controlled, thus realizing customized production of the comprehensive performance of the arc-proof fabric, such as the protective level, wear resistance, and softness, to meet the specific protective needs in different working environments. The method has a clear process route and controllable raw material costs, and has good prospects for industrial application. DETAILED DESCRIPTION
[0020] In order to make the objects, technical solutions and advantages of the present application clearer, the technical solutions of the present application will be described in detail below. Obviously, the described embodiments are only some of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative work belong to the protection scope of the present application.
[0021] Described in the specification is an arc-proof fabric and a preparation method thereof. The method aims to endow the fabric with excellent and durable arc-proof performance without significantly sacrificing the original wearing performance of the fabric by constructing a three-dimensional porous composite protection network integrated with the fiber structure in situ inside the fabric substrate. The entire preparation process is systematically divided into four core steps: substrate pretreatment and surface activation, multi-stage precursor solution infiltration and loading, in-situ hydrothermal synthesis and thermal shock molding of the integrated protection network, and final finishing and setting.
[0022] Specifically, the starting step of the preparation process is step S1, i.e. the substrate pretreatment and surface activation step. The core purpose of this step is to create the necessary physical and chemical basis for the firm anchoring of the subsequent functional network. First, in the selection of the substrate, in order to ensure that the fabric itself has basic flame-retardant performance, thereby forming a synergistic effect with the protection network constructed subsequently, the present application selects a fabric composed of inherently flame-retardant fibers as the base fabric. In a specific embodiment, the base fabric is a woven fabric woven from meta-aramid fiber and para-aramid fiber blended yarns. Meta-aramid fiber, due to its excellent heat stability and insulation, constitutes the main body of the base fabric; while para-aramid fiber, with its extremely high strength and modulus, provides the fabric with excellent tear resistance and dimensional stability. In order to further optimize the anti-static performance of the fabric and provide a basis for the electrical performance of the subsequent composite network, a certain proportion of conductive fibers are also mixed into the yarns. As an optimal ratio scheme, the yarns are composed of meta-aramid fiber and para-aramid fiber in a mass ratio of (90-95):(5-8), and (1-3) of conductive fibers. By using such blended yarns, woven through specific fabric organization structures such as two over one under or three over one under twill weave, a woven fabric base fabric with compact structure but still maintaining a certain degree of flexibility can be obtained. The areal density of the base fabric is precisely controlled within the range of 180-260 g / m2, which is an optimal interval that ensures the basic protection strength while avoiding the fabric being too thick and heavy, thereby maintaining good wearing comfort.
[0023] After the base fabric is selected, surface activation treatment is performed. Because the aramid fiber surface has highly inert chemical properties, is smooth, and is difficult to effectively combine with foreign substances, it must be modified. The present application uses low-temperature plasma glow discharge treatment technology. The selected base fabric is placed in a large vacuum plasma treatment device in a roll-to-roll mode. The device chamber is first evacuated to a high vacuum state to exclude the influence of other impurity gases in the air. Then, a predetermined mixed atmosphere is introduced into the chamber.
[0024] The mixed atmosphere is composed of inert gas and active gas. The inert gas, such as argon, mainly functions to generate a nanoscale rough etching structure on the fiber surface through physical bombardment by high-energy ions, increasing the specific surface area and providing a basis for subsequent physical adsorption and mechanical interlocking of substances. The active gas, such as oxygen, functions to form highly active oxygen-containing radicals in the plasma state, which react with the aramid molecular chains broken by argon ion bombardment to graft a large number of oxygen-containing active functional groups on the fiber surface. In a specific process parameter setting, the mixed atmosphere is composed of argon with a volume flow rate of 80-120 standard cubic centimeters per minute (sccm) and oxygen with a volume flow rate of 10-30 standard cubic centimeters per minute (sccm). The radio frequency power of the glow discharge is set to 200-400 watts, and the vacuum degree in the treatment chamber is maintained at 15-50 Pa under gas dynamic equilibrium. The treatment time is precisely controlled according to the fabric travel speed to ensure the uniformity of the treatment of each part of the fabric, and is usually 90-240 seconds. After this step, the originally smooth and inert aramid fiber surface is successfully etched with nanoscale grooves, and hydrophilic active functional groups mainly containing hydroxyl (-OH) and carboxyl (-COOH) are successfully grafted. These functional groups not only greatly improve the wettability of the fiber surface, but more importantly, they will serve as "anchor points" for the subsequent chemical bonding of the inorganic network, laying the foundation for the molecular-level connection of the protective network and the base fabric fibers.
[0025] The next step is step S2, which is a multi-stage precursor solution infiltration and loading step. This step is the process of introducing the precursors of the two core components required to build the composite protective network, and the depth and uniformity of the infiltration directly determine the integrity and performance of the final protective network. This step includes first precursor infiltration and loading and second precursor infiltration and loading. First, the first precursor infiltration and loading is performed, which aims to uniformly coat the two-dimensional nanosheet material on the surface of each single fiber of the base fabric and fill the small interstitial spaces inside the fiber bundle. The present application preferably uses graphene oxide (GO) as the two-dimensional nanosheet material. Graphene oxide is a product obtained by treating graphite with a strong oxidizing agent, and has abundant oxygen-containing functional groups on its sheet structure, allowing it to form a stable colloidal dispersion in water and be easily processed.
[0026] The graphene oxide used can be prepared by a modified Hummers method. By controlling the degree of oxidation and subsequent centrifugal purification process, single sheet transverse size distribution between 0.5 microns to 5 microns and thickness of 0.8 nanometers to 1.2 nanometers of graphene oxide is selected. The graphene oxide in this size range can effectively coat the fibers and is not prone to excessive aggregation between fibers. The graphene oxide is uniformly dispersed in deionized water to prepare a first precursor solution with a mass concentration of 1.0 mg / ml to 5.0 mg / ml. The substrate treated by the surface activation process in step S1 is completely immersed in the graphene oxide aqueous dispersion. In order to overcome the liquid surface tension and ensure that the solution can penetrate the tight yarn structure, the penetration process is assisted by ultrasonic oscillation treatment. In a specific embodiment, a 40 kHz ultrasonic bath is used, and the oscillation lasts for 30 minutes to 90 minutes. The cavitation effect generated by high-frequency oscillation can effectively open the fiber bundle and force the graphene oxide layers to enter the nanoscale and microscale gaps between the fibers with the water flow. Since the fiber surface has hydrophilicity after plasma treatment, the oxygen-containing functional groups on the graphene oxide layers will uniformly adsorb and coat the surface of the single fiber through hydrogen bonding.
[0027] After the immersion is completed, the fabric is subjected to a double roller mill to remove the excess, unabsorbed solution on the surface of the fabric and in the interstitial gaps of the fibers. The pressure of the roller mill is precisely adjusted to control the mill pick-up rate to between 70% and 95%. Precise control of the mill pick-up rate is a key process point to ensure uniform loading of graphene oxide.
[0028] After the first precursor loading is completed, the graphene oxide-loaded substrate is immediately subjected to a second precursor penetration loading. The second precursor serves to introduce the chemical precursor of the inorganic network skeleton. The present application uses a sol-gel precursor solution as the second precursor solution. The preparation process of this solution itself is a precise chemical process. In a typical preparation scheme, 100 parts by weight of anhydrous ethanol is first used as the main solvent, as it can be well miscible with the metal alkoxide precursor added later. 10-15 parts by weight of tetraethyl orthosilicate (TEOS) is added as the main source of silica network, and 1-3 parts by weight of aluminum isopropoxide is added as the source of alumina network, which also serves to improve the performance of the final ceramic phase. The above components are thoroughly mixed under magnetic stirring. Subsequently, the entire system is placed in an ice water bath for cooling, in order to control the rate of the subsequent hydrolysis reaction and avoid rapid polymerization of the precursor leading to gelation. Under low temperature and continuous stirring, 4-8 parts by weight of deionized water is slowly added dropwise to the mixed solution as a necessary reactant for the hydrolysis reaction.
[0029] Meanwhile, in order to catalyze the hydrolysis and condensation reactions and maintain the stability of the system, 0.2-0.6 parts by weight of 1 mol / L hydrochloric acid is also added dropwise. As an acid catalyst, the hydrochloric acid can promote the hydrolysis of alkoxides such as TEOS and control the morphology of the condensation product. After the dropwise addition is completed, the reaction is continued under ice water bath conditions for 2-4 hours until all components are completely reacted to form a clear, transparent, uniform and stable sol-gel precursor solution. The graphene oxide-loaded fabric is directly immersed in the freshly prepared solution. Since the solution is solvented in alcohol, its surface tension is low and its permeability is extremely strong, allowing it to further penetrate into the interstitial space occupied by the graphene oxide layers and come into close contact with the loaded graphene oxide layers. After immersion, the liquid is also rolled by the double roller car, and the rolling rate is controlled in the range of 80% to 100%. At this point, the two precursors, graphene oxide nanosheets and sol-gel solution, have coexisted in the fiber structure of the fabric, preparing for the next step of in-situ synthesis.
[0030] The subsequent step S3 is the in-situ hydrothermal synthesis and thermal shock molding step of the integrated protective network, which is the most core part of the technical scheme of the present application and is directly related to the formation of the microstructure and macroscopic performance of the final protective network. This step is divided into two stages of hydrothermal reaction and thermal shock molding. First, the hydrothermal reaction is carried out. The fabric loaded with the two precursors in step S2 is placed flat in a sealed high-pressure reaction kettle lined with polytetrafluoroethylene or hastelloy. A certain amount of pure water is injected into the reaction kettle to provide a high-temperature and high-pressure steam environment required for the hydrothermal reaction. In a specific process setting, the mass ratio of fabric to pure water is controlled to be 1:20 to ensure sufficient water to participate in the reaction and provide uniform heat transfer medium. The filling degree of the reaction kettle is controlled at about 75% to form a saturated vapor pressure after heating. After sealing the reaction kettle, it is placed in an oven for programmed heating until the target temperature range of 140-180°C is reached, and then kept at this temperature for 4-8 hours. In such a high-temperature and high-pressure water environment, a series of complex physical and chemical changes occur. On the one hand, the sol-gel precursor introduced in step S2, i.e. tetraethyl orthosilicate and aluminum isopropoxide, undergoes intense hydrolysis and condensation reactions. The reaction generates a silica-alumina composite hydrogel network in-situ on the surface of aramid fibers and the adsorbed graphene oxide layers.
[0031] The network grows and coats the fiber surface like a vine, filling the interstitial spaces between the fibers and firmly "welding" the graphene oxide layers into the fiber structure. On the other hand, under hydrothermal conditions, some of the unstable oxygen-containing functional groups on the surface of graphene oxide are reduced, a process known as hydrothermal reduction, causing the graphene oxide to gradually transform into reduced graphene oxide (rGO) with better electrical conductivity. After the hydrothermal reaction is complete, the pressure is released and the temperature is lowered, and the base fabric is removed. At this point, the base fabric has been loaded with a composite structure composed of rGO and a hydrogel network. Subsequently, the base fabric is subjected to preliminary drying treatment, such as drying in an oven at 80 degrees Celsius, to remove most of the physically adsorbed water.
[0032] After drying, the base fabric immediately enters the thermal shock molding stage. The purpose of this stage is to convert the two-dimensional rGO layers into a three-dimensional porous structure and to ceramize the hydrogel network. This process is carried out in a tubular rapid thermal annealing furnace, which must have the ability to provide inert atmosphere protection and ultra-high heating rate.
[0033] First, the treated base fabric is placed in the constant temperature zone of the furnace, and after sealing the furnace, pure nitrogen or argon gas with a purity of 99.999% is continuously introduced into the furnace at a flow rate sufficient to expel and reduce the oxygen concentration in the furnace to less than 5 parts per million (5 ppm). The purpose of establishing and maintaining an inert atmosphere is to prevent oxidation and ablation of aramid fibers and graphene during subsequent high-temperature processing. After the atmosphere is stable, start the rapid heating program to rapidly raise the furnace temperature from room temperature to a target peak temperature of 200 to 300 degrees Celsius at an ultra-high heating rate of more than 30 degrees Celsius per second.
[0034] When the furnace temperature reaches the preset target temperature, it is kept constant for 30 to 120 seconds. During this momentary "thermal shock" process, the residual oxygen-containing functional groups (such as epoxy and hydroxyl groups) between the rGO layers and at the interface between the layers and the fibers will instantaneously decompose upon heating, generating a large amount of carbon dioxide and water vapor. The explosive generation of these gases, like countless micro "airbags" expanding between the rGO layers, generates a huge instantaneous pressure that drives the rGO layers to peel off each other, undergo violent expansion and wrinkling, thereby transforming from the original stacked two-dimensional sheet structure into a three-dimensional graphene foam structure that is interconnected and rich in micrometer- and nanometer-sized pores. At the same time, the silica-alumina hydrogel network formed in the hydrothermal stage dehydrates and rapidly sinters at such a high temperature, transforming into an inorganic ceramic network skeleton with a certain crystalline or amorphous phase. This ceramic network and the graphene foam structure formed by expansion are spatially interpenetrated and entangled with each other, and finally solidified to form a three-dimensional porous composite protective network that is deeply anchored to the fiber structure of the base fabric and inseparable. After processing, the fabric is removed under inert atmosphere protection and cooled to room temperature.
[0035] The last step of the preparation process is step S4, the finishing and setting step. This step aims to improve the hand and appearance of the fabric after a series of chemical and physical treatments, and to stabilize its size. The composite fabric formed after step S3 is placed in an ultrasonic cleaning tank containing deionized water and subjected to several ultrasonic cleanings. The purpose is to thoroughly remove any unreacted residues, byproducts and impurities that may have been produced during the reaction process and that are only attached to the surface of the fabric by physical adsorption. After cleaning, the fabric is dewatered and then subjected to softening finishing treatment. Softening finishing is the use of a chemical finishing agent that has no adverse effect on the protective properties of the fabric to restore and optimize the hand of the fabric. The present application preferably uses an amino-modified polysiloxane microemulsion as a softening agent. The dewatered fabric is padded with the softening agent working solution, uniformly pressed by a mangle, and then introduced into a drying machine for pre-drying at a temperature of about 100 degrees Celsius for 10 minutes to allow the softening agent molecules to be initially spread on the surface of the fibers. Finally, the fabric is introduced into a heat setting machine and subjected to heat setting treatment at 150 degrees Celsius for 3 minutes in a stretched state. Heat setting not only allows the softening agent molecules to crosslink with the fibers to form a washable softening effect, but also eliminates the internal stress generated in the fabric during the entire processing process, giving it stable size and good drape.
[0036] At this point, the entire preparation process of the anti-electric arc fabric is completed, and the finished product is finally obtained.
[0037] Correspondingly, the present application also provides an anti-electric arc fabric prepared by the above method. The fabric retains the form of the base fabric on a macroscopic scale, but fundamentally changes the microstructure. Its structural feature is that it is composed of a base fabric and a three-dimensional porous composite protective network integrated inside the base fabric. The base fabric, as described above, is a woven or knitted fabric composed of inherently flame-retardant fibers, preferably aramid fibers, which provides the basic mechanical framework and flame retardancy for the entire composite fabric. The three-dimensional porous composite protective network is the core functional unit that gives the fabric excellent anti-electric arc performance. This network is not simply attached to the surface of the fabric, but conformally coats the surface of each individual fiber of the base fabric on a microstructural scale, and almost completely fills all the three-dimensional gaps between fibers and yarns. It forms an inseparable whole structure with the base fabric fibers through two mechanisms: one is the chemical bonding between the active functional groups formed in the plasma activation step and the inorganic network precursors generated in the hydrothermal synthesis stage; the other is the physical and mechanical interlocking effect of the protective network generated, grown and solidified in situ in the fiber gaps. These two mechanisms together ensure that the protective network remains firmly inside the fabric and does not fall off when the fabric is subjected to repeated bending, rubbing and washing.
[0038] More specifically, the internal structure of the three-dimensional porous composite protective network is composed of two functionally complementary, structurally interpenetrating and synergistic components.
[0039] The first component is a three-dimensional porous thermally conductive skeleton composed of reduced graphene oxide. The thermally conductive skeleton presents a continuous, sponge-like or foam-like network structure inside the fabric. Its structural feature is to have multi-level pores from nanoscale to microscale. This structure gives the skeleton a very high specific surface area and a very low area density. Functionally, due to the ultra-high intrinsic thermal conductivity of graphene itself, this continuous thermally conductive skeleton actually forms a throughout, high-efficiency heat conduction path inside the fabric. When a point on the surface of the fabric encounters a sudden high-intensity heat flow impact such as an electric arc, the concentrated heat can be instantaneously absorbed by the thermally conductive skeleton in nanoseconds to picoseconds, and quickly conducted and dissipated along the two-dimensional plane and three-dimensional space direction of the graphene network, thereby effectively preventing the high accumulation of heat at the impact point, rapidly converting the point heat impact into a surface heat distribution, greatly reducing the local temperature, and preventing the rapid decomposition of the base fabric fibers due to instantaneous ultra-high temperature. In addition, under the direct action of the electric arc high temperature, the surface layer of the graphene skeleton will quickly transform into a more dense amorphous carbon layer, which can effectively act as a physical barrier, on the one hand to isolate subsequent heat radiation, and on the other hand to prevent molten metal droplets that may exist in the arc from penetrating the fabric and causing secondary harm to the human body.
[0040] The second component is an inorganic ceramic reinforcing phase interpenetrated with the thermally conductive skeleton and anchored to the base fabric fibers. The reinforcing phase is essentially a three-dimensional network structure composed of nanoscale silica-alumina composite oxides. Under normal conditions, the presence of this ceramic network provides the entire composite protective network with excellent mechanical strength, structural rigidity and wear resistance, effectively improving the fabric's wear resistance. However, its role is even more critical when it comes to extreme high-temperature conditions such as electric arcs. Since both silica and alumina are inorganic materials with extremely high melting points (about 1700°C and 2050°C, respectively), the ceramic reinforcing phase can still maintain its structural integrity at higher temperatures where the graphene skeleton may ablate. It acts like a steel skeleton in construction, effectively supporting the entire protective network and suppressing the melting and deformation of the base fabric aramid fibers under high temperature and the possible rupture and pulverization of the graphene skeleton after carbonization, thereby eliminating the possibility of molten droplets in traditional flame-retardant fabrics under high temperature. The stability of this structure ensures that the fabric can always provide a stable and reliable physical barrier for the wearer throughout the electric arc exposure process.
[0041] As a preferred embodiment of the present application, the specific parameters of the anti-arc fabric can be configured as follows: the base cloth is woven by 93% mass fraction of meta-aramid fiber, 5% mass fraction of para-aramid fiber and 2% mass fraction of conductive fiber blended yarn, using two over one under right twill weave, and the areal density is accurately controlled to be 220 grams per square meter.
[0042] After the whole set of process treatment, the total load of the three-dimensional porous composite protection network constructed accounts for 10% to 25% of the final total mass of the fabric. Through statistical analysis of the SEM images, the pore size in the reduced graphene oxide heat conducting skeleton presents a multi-level distribution, covering a range of 50 nanometers to 5 micrometers. In the inorganic ceramic reinforced phase, by accurately controlling the feeding ratio of TEOS and aluminum isopropoxide in the precursor solution, the molar ratio of silicon dioxide to aluminum oxide in the finally formed composite oxide is controlled at about 10:1. Through X-ray photoelectron spectroscopy (XPS) analysis, it can be confirmed that there is a C-O-Si chemical bond formed in the plasma activation step between the interface region of the protection network and the aramid fiber of the base cloth, which provides direct chemical evidence for the firm combination of the two. Embodiment
[0043] The present embodiment provides a specific preparation process of an anti-arc fabric.
[0044] (1) Substrate pretreatment and surface activation: select a base cloth made of 32 yarns of 93% mass of meta-aramid fiber, 5% mass of para-aramid fiber and 2% mass of P-150 type carbon core conductive fiber blended, woven by 2 / 1 twill weave, with an areal density of 220 grams per square meter. Place the base cloth in the chamber of a roll-to-roll vacuum plasma treatment equipment (model: HD-2000). The chamber is evacuated to 5 Pa. Then, high-purity argon and high-purity oxygen are introduced into the chamber, with the argon volume flow rate controlled at 100 standard cubic centimeters per minute (sccm) and the oxygen volume flow rate controlled at 20 standard cubic centimeters per minute (sccm). Start the radio frequency power supply and set the glow discharge power to 300 watts, at which time the dynamic vacuum degree in the chamber is maintained at 30 Pa. Control the fabric running speed so that the exposure time of the fabric in the plasma region is 180 seconds. After treatment, take out after 5 minutes in vacuum environment.
[0045] (2) Multi-stage precursor solution infiltration and loading: First, a first precursor solution is prepared. Graphene oxide (GO) is prepared using a modified Hummers method, and its single sheet lateral size is mainly distributed in 1-3 microns and the thickness is about 1.0 nanometer measured by atomic force microscopy (AFM). The GO powder is dispersed in deionized water, and after ultrasonic treatment, a GO water dispersion with a mass concentration of 3.0 mg / ml is prepared. The aramid fabric treated in step (1) is immersed in the solution and continuously oscillated in a 40 kHz ultrasonic cleaning tank for 60 minutes. After taking out, the liquid is rolled by a double roller, and the pressure of the roller is controlled to make the rolling rate 85%.
[0046] Subsequently, a second precursor solution is prepared. 1000 grams of anhydrous ethanol is taken as the solvent, and under magnetic stirring, 120 grams of tetraethyl orthosilicate (TEOS) and 20 grams of aluminum isopropoxide are sequentially added, and stirred for 30 minutes to make them uniformly mixed. The mixed beaker is placed in an ice water bath, and under continuous stirring, 60 grams of deionized water is slowly added dropwise. After the dropwise addition is completed, 4 grams of hydrochloric acid solution with a concentration of 1 mole / liter is slowly added dropwise. The dropwise addition process is controlled to be completed within 30 minutes. Subsequently, the reaction is continued for 3 hours in the ice water bath and under stirring to obtain a clear and transparent sol-gel precursor solution. The GO-loaded fabric is immersed in the solution for 20 minutes, and then the liquid is rolled by the same double roller, and the rolling rate is controlled to be 90%.
[0047] (3) In-situ hydrothermal synthesis and thermal shock molding of integrated protective network: The fabric (100 grams in mass) treated in step (2) is placed in a 2.5 liter volume Hastelloy-lined high-pressure reaction kettle, and 2000 grams of pure water is added. The reaction kettle is sealed, and after checking the airtightness, it is placed in a programmed temperature oven. The program is set to heat at a rate of 5 degrees Celsius per minute to 160 degrees Celsius, and to keep the temperature constant at this temperature for 6 hours. After the reaction is completed, it is naturally cooled to room temperature, and after pressure relief, the fabric is taken out. The taken-out fabric is dried in an oven at 80 degrees Celsius for 4 hours.
[0048] The dried fabric is placed in a quartz tube of a tube-type rapid thermal annealing furnace (model: RTA-1200). The quartz tube is sealed, and high-purity nitrogen gas is introduced at a flow rate of 500 sccm for 30 minutes to completely replace the air in the tube. Then, the heating program is started, and the furnace temperature is rapidly heated from room temperature to 300 degrees Celsius at a heating rate of 30 degrees Celsius per second. After reaching 300 degrees Celsius, the temperature is kept constant for 60 seconds. After the treatment is completed, it is naturally cooled to room temperature under the protection of nitrogen atmosphere, and the composite fabric is taken out.
[0049] (4) Finishing and setting: The obtained composite fabric was washed in deionized water for 3 times, each for 20 minutes. After washing, the fabric was centrifuged to remove water. A softener working solution was prepared using an amino-modified polysiloxane microemulsion (model: SF-8411) with a concentration of 30 grams per liter. The centrifuged fabric was padded with the working solution at a pick-up rate of 80%. Then it was pre-dried at 100 degrees Celsius for 10 minutes, and finally heat-set on a tentering machine at 150 degrees Celsius for 3 minutes. The final anti-arc fabric of Example 1 was obtained.
[0050] Comparative Example 1 This comparative example aims to compare with Example 1, the main difference being the use of a traditional coating finishing method instead of the in-situ integrated synthesis method.
[0051] (1) Substrate: The same aramid fabric (93% meta-aramid / 5% para-aramid / 2% conductive fiber, 220 grams per square meter) as in Example 1 was used. No plasma activation treatment was performed on the substrate.
[0052] (2) Preparation of coating slurry: 30 grams of commercially available water-based polyurethane emulsion (PU) was taken and diluted with 60 grams of deionized water. Separately, 3 grams of reduced graphene oxide powder (rGO) and 2 grams of nano-silica powder were taken and dispersed in water with a small amount of dispersant for 1 hour using high-intensity ultrasonic dispersion, obtaining a mixed filler dispersion. The filler dispersion was slowly added to the diluted PU emulsion and stirred at high speed for 2 hours to obtain a uniform coating slurry. The total mass of the fillers was equivalent to the loading amount of the protective network in Example 1.
[0053] (3) Coating and post-treatment: The coating slurry prepared in step (2) was uniformly coated on one surface of the aramid fabric using a doctor blade coating method, controlling the dry weight of the coating to be about 18% of the total weight of the final fabric. The coated fabric was pre-dried at 80 degrees Celsius for 15 minutes, and then cured by baking at 160 degrees Celsius for 5 minutes. The final anti-arc fabric of Comparative Example 1 was obtained.
[0054] Performance testing and data comparison The fabric samples prepared in Example 1 and Comparative Example 1, as well as the original aramid fabric without any treatment, were subjected to performance testing according to relevant standards. The test items included arc protection performance (ATPV), washing durability, air permeability, and softness. Washing was performed according to ISO 6330 standard for 50 cycles. The test results are summarized in the table below: Test item Test standard Original base cloth Example 1 (after treatment) Example 1 (after 50 times washing) Comparative example 1 (after treatment) Comparative example 1 (after 50 times washing) Appearance and structure SEM Smooth fiber surface Protective network fills fiber gap, integrated with fiber Network structure is complete, no shedding Surface forms discontinuous coating, clear fiber interface Coating cracks and peels off in large area Area density (g / m²) GB / T 4669 220 265 263 268 235 Arc protection value (ATPV, cal / cm²) ASTM F1959 5.2 18.5 17.9 16.8 7.1 ATPV retention rate (%) - - - 96.8% - 42.3% Air permeability (mm / s) GB / T 5453 125 88 85 45 102 Bending stiffness (mN·cm) GB / T 18318.1 18.2 25.6 26.1 48.5 22.3 Limiting oxygen index (LOI, %) GB / T 5454 31 >45 >45 42 33 From the data comparison of the above table, it can be clearly seen that the arc-proof fabric prepared in Example 1 has an ATPV value of 18.5 cal / cm2, which is much higher than the original base fabric and is at a high level compared with Comparative Example 1 using the coating method. Most importantly, after undergoing 50 standard industrial washing cycles, the ATPV value of Example 1 only has a slight decrease, with a retention rate as high as 96.8%, and its area density and microstructure remain basically unchanged, which fully proves that the protective network synthesized in situ has extremely excellent durability and washing resistance. In contrast, after washing, the fabric of Comparative Example 1 has a sharp decrease in ATPV value to 7.1 cal / cm2 due to the serious peeling of the surface coating, and almost loses the effective arc protection ability, with an ATPV retention rate of only 42.3%. In terms of comfort-related indicators, although the air permeability of Example 1 decreases, it still remains at a good level of 88 mm / s, while the initial air permeability of Comparative Example 1 is extremely poor due to the complete sealing of the surface by the coating. After washing, the air permeability and bending stiffness of Comparative Example 1 recover to a level close to the original base fabric due to the peeling of the coating, but this is exactly the evidence of the failure of its protective performance. Although the bending stiffness of Example 1 increases, it is still within an acceptable soft range, which is much better than the stiff feel of Comparative Example 1 in the initial state. These data objectively confirm that the technical solution of the present application has significant superiority in achieving the synergistic and unified performance of high-efficiency and long-lasting protection and maintaining good wearing comfort.
Claims
1. A method for preparing an anti-arc fabric, characterized in that, The method includes the following steps: Step S1, Substrate Pretreatment and Surface Activation Step: Select a base fabric made of inherently flame-retardant fibers, place the base fabric in a vacuum plasma treatment device, and perform low-temperature plasma glow discharge treatment in a mixed atmosphere of inert gas and active gas to etch and graft oxygen-containing active functional groups on the surface of a single fiber of the base fabric. Step S2, Multi-stage precursor solution permeation and loading step: The first precursor and the second precursor are permeated and loaded sequentially into the base fabric treated in step S1, wherein the first precursor is a dispersion containing two-dimensional nanosheet material, and the second precursor is a solution formed by dissolving an inorganic network framework chemical precursor in a solvent. Step S3, in-situ synthesis and molding of the integrated protective network: The base fabric loaded with two precursors in step S2 is subjected to hydrothermal reaction treatment to cause the chemical precursor in the second precursor to undergo hydrolysis and condensation reaction, and an inorganic oxide network is generated in-situ on the fiber surface and fiber gaps of the base fabric; Subsequently, the base fabric is subjected to high-temperature rapid thermal shock treatment to cause the two-dimensional nanosheet material to peel off and expand, forming a three-dimensional porous structure, which is interconnected with the inorganic oxide network to jointly form a three-dimensional porous composite protective network deeply anchored to the fiber structure of the base fabric; Step S4, finishing and setting steps: The composite fabric formed after step S3 is washed, softened and heat-set to finally obtain the anti-arc fabric.
2. The method for preparing the arc-resistant fabric according to claim 1, characterized in that, In step S1, the base fabric is a woven fabric made of yarn composed of a blend of meta-aramid fibers and para-aramid fibers in a mass ratio of (90-95):(5-8) and conductive fibers in a mass ratio of (1-3). The fabric has an areal density of 180 g / m² to 260 g / m². The mixed atmosphere used in the low-temperature plasma treatment is composed of argon gas with a volumetric flow rate of 80-120 standard cubic centimeters / minute and oxygen gas with a volumetric flow rate of 10-30 standard cubic centimeters / minute. The power of the glow discharge treatment is 200 watts to 400 watts, the vacuum degree in the treatment chamber is maintained at 15 Pa to 50 Pa, and the treatment time is 90 seconds to 240 seconds.
3. The method for preparing the arc-resistant fabric according to claim 1, characterized in that, In step S2, the first precursor solution is an aqueous dispersion of graphene oxide, wherein the transverse dimension of a single graphene oxide sheet is 0.5 micrometers to 5 micrometers, the thickness is 0.8 nanometers to 1.2 nanometers, and the mass concentration of the aqueous dispersion is 1.0 mg / mL to 5.0 mg / mL. Furthermore, during the process of immersing the base fabric in the first precursor solution, ultrasonic oscillation at a frequency of 40 kHz is applied for oscillation time of 30 to 90 minutes. After immersion, excess solution is removed by a rolling device, and the rolling residue rate of the rolling device is controlled between 70% and 95%.
4. The method for preparing the arc-resistant fabric according to claim 3, characterized in that, The second precursor solution is a sol-gel precursor solution, which is prepared as follows: 100 parts by weight of anhydrous ethanol is used as the main solvent, and 10-15 parts by weight of tetraethyl silicate and 1-3 parts by weight of aluminum isopropoxide are added to it. After mixing evenly, 4-8 parts by weight of deionized water are added to the mixed solution under ice-water bath conditions, and 0.2-0.6 parts by weight of hydrochloric acid with a concentration of 1 mol / L is added dropwise as a catalyst. The reaction is continuously stirred for 2 to 4 hours. After the base fabric loaded with graphene oxide is impregnated in the solution, it is rolled by a rolling device, and the roll-off rate is controlled at 80% to 100%.
5. The method for preparing the arc-resistant fabric according to claim 1, characterized in that, In step S3, the hydrothermal reaction treatment conditions are as follows: in a high-pressure reactor, the mass ratio of the base fabric to pure water is controlled at 1:20, the reactor is heated to a temperature of 140°C to 180°C, and the reaction is maintained at this temperature for 4 to 8 hours; and the high-temperature rapid thermal shock treatment is carried out under an inert atmosphere, with the furnace temperature rapidly increased from room temperature to a target temperature of 200°C to 300°C at a heating rate greater than 30°C / second, and maintained at this target temperature for 30 to 120 seconds.
6. An anti-arc fabric, characterized in that, The fabric includes: A base fabric made of inherently flame-retardant fibers; and an integrated three-dimensional porous composite protective network constructed inside the base fabric. The three-dimensional porous composite protective network conformally covers the surface of a single fiber of the base fabric in terms of microstructure and fills the three-dimensional gaps between fibers and yarns. Through chemical bonding and physical-mechanical interlocking, it forms an inseparable integral structure with the fibers of the base fabric. The three-dimensional porous composite protective network consists of the following two interpenetrating components: A three-dimensional porous thermally conductive framework composed of reduced graphene oxide; and an inorganic ceramic reinforcing phase composed of nanoscale composite oxides that intersects with and is anchored to the base fabric fibers.
7. The arc-resistant fabric according to claim 6, characterized in that, The three-dimensional porous thermally conductive framework is a continuous foam-like network with micron- and nano-level multi-level pore structures. It forms a through-type channel with high thermal conductivity inside the fabric, which can quickly conduct and dissipate concentrated heat flow when subjected to high-temperature impact from electric arcs. Furthermore, its surface layer can be transformed into a dense carbonaceous layer at high temperatures. The inorganic ceramic reinforcing phase is a three-dimensional network structure composed of silicon dioxide-alumina composite oxides. It can maintain the structural integrity of the entire protective network under extreme high-temperature conditions and inhibit the melting and shrinkage of the base fabric fibers and the rupture of the carbonized layer.
8. The arc-resistant fabric according to claim 6 or 7, characterized in that, The base fabric is a woven fabric made of a blended yarn of 93% by mass of meta-aramid fiber, 5% by mass of para-aramid fiber and 2% by mass of conductive fiber; the total load of the three-dimensional porous composite protective network accounts for 10% to 25% of the final total mass of the fabric; the pores in the reduced graphene oxide thermally conductive skeleton have a pore size distribution range of 50 nanometers to 5 micrometers; and in the inorganic ceramic reinforcing phase, the molar ratio of silicon dioxide to alumina is 10:
1.
9. The arc-resistant fabric according to claim 6, characterized in that, The three-dimensional porous composite protective network and the inherently flame-retardant fibers of the base fabric are chemically bonded together by CO-Si chemical bonds formed by the reaction of oxygen-containing active functional groups grafted onto the fiber surface during plasma activation treatment with the precursor of the inorganic ceramic reinforcing phase.
10. The method according to claim 1, characterized in that, In step S4, the softening finishing process involves using an amino-modified polysiloxane microemulsion as a softener, immersing the washed and dehydrated fabric in the softener working solution, pre-drying it at 100 degrees Celsius, and finally performing a heat setting treatment at 150 degrees Celsius.
Citation Information
Patent Citations
Arc protection fabric, manufacturing method and application thereof
CN101973148A
Preparation method of arc protection coating fabric
CN116289236A